Some late Wenlock and Ludlow monograptid graptolites, Cornwallis Island, Arctic Canada - Lenz, Alfred C. (Canadian Journal of Earth Sciences, 1992)
Seven species of uncompressed latest Wenlock and Ludlow monograptid graptolites, isolated from calcareous concretions, are described and illustrated. The biostratigraphically important species "Pristiograptus" ludensis, of latest Wenlock age, and Saetograptus fritschi linearis and Monograptus ceratus, of mid-Ludlow age, are illustrated in uncompressed form for the first time. The remaining species described include Bohemograptus bohemicus tenuis, Colonograptus colonus, Saetograptus ex gr. chimaera, and Pristiograptus dalejensis, all of Ludlow age. The last-named species is the most common but is biostratigraphically long ranging.